Sameness and/or otherness: what matters more for narcissist CEOs in the context of non-market strategy? - Alshammari, Marwan Ahmad (Journal of business ethics, 2025)
The purpose of the current paper is to introduce the theoretical arguments of optimal distinctiveness literature in studying the relationship between CEO narcissism and corporate social responsibility. We focus on CSR scope conformity and CSR emphasis differentiation and introduce CEO narcissism as an important determinant of the extent to which the firm responds to these two types of strategic pressures. Our analysis is based on a sample of 509 firm-year observations over the 2006-2013 period. Fixed effects regression technique is used to test our hypotheses. Our findings provide evidence that CEO narcissism is negatively related to CSR conformity and positively related to CSR differentiation strategies. We also find evidence that firm prior performance will moderate the relationship between CEO narcissism and CSR conformity but not CSR differentiation.